Economic woman : demand, gender, and narrative closure in Eliot and Hardy - Kreisel, Deanna K. (University of Toronto Press, 2012)
"The ways in which women are portrayed in Victorian novels can provide important insights into how people of the day thought about political economy, and vice versa. In Economic Woman, Deanna K. Kreisel innovatively shows how images of feminized sexuality in novels by George Eliot and Thomas Hardy reflected widespread contemporary anxieties about the growth of capitalism.